In charge : finding the leader within you - Munroe, Myles (New York : Faith Words, 2008)
The book helps one discover how leadership is: predetermined, not based on your preferences; a position prepared for you by God Himself; costly in terms of time, training, and the process of refinement; inherent as your birthright; a divine deposit revealed in your particular gifts; not for you but for others; about becoming yourself for the benefit of others.
Includes bibliographical references (p. 201).
rua 25/04/17
Loans.
Keywords: Leadership; Leadership - religious aspects; Self-actualization (Psychology)